Integrating Teacher Professional Ethics, Guidance Counseling, and School Management for 21st Century Education: A Systematic Review - Mahlaini Azizah Harahap; Chardinal. DV; Eggi Martiansyah; Syarifuddin; Feralia Eka Putri (CAHAYA: Journal of Research on Science Education, 2026)
This study aims to analyze the urgency of integrating teacher professional ethics, guidance and counseling, and school management in facing the challenges of 21st-century education. This study used the Systematic Literature Review (SLR) method with planning, conducting, and reporting stages. Data were obtained from various scientific journals published between 2022 and 2026 through databases such as Google Scholar. The initial search results found 100 articles, which were then selected based on inclusion and exclusion criteria, resulting in 24 articles worthy of analysis. The results show that teacher professional ethics plays a role in shaping character and professionalism, guidance and counseling supports the holistic development of students, and school management is a key factor in improving the quality of education. The integration of these three aspects is crucial for creating an education system that is adaptive, innovative, and oriented to the needs of the 21st century.